2003
DOI: 10.1093/jee/96.3.609
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Cerotoma arcuatus (Coleoptera: Chrysomelidae) and Field Validation of a Laboratory Model for Temperature Requirements

Abstract: Cerotoma arcuatus Olivier is a polyphagous pest of legumes [soybean, Glycine max (L.); dry beans, Phaseolus vulgaris (L.); and cowpeas, Vigna unguiculata (L.)], all of which are considered important protein sources for humans and domestic animals. Studies on the biology and temperature requirements of C. arcuatus were made under laboratory and field (cage) conditions. In the laboratory, insects were reared on soybean plants in incubators held at 18, 20, 22, 25, 28, 30, or 32 degrees C, 70 +/- 10% RH, and a pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…In our study, there was no need of the Arrhenius equation to fit the data. Other authors came to comparable conclusions with coleopteran invertebrates (Nava & Parra, 2003). They showed that, in the range 18-32°C, the duration of the instars was inversely proportional to the temperature.…”
Section: Discussionmentioning
confidence: 62%
“…In our study, there was no need of the Arrhenius equation to fit the data. Other authors came to comparable conclusions with coleopteran invertebrates (Nava & Parra, 2003). They showed that, in the range 18-32°C, the duration of the instars was inversely proportional to the temperature.…”
Section: Discussionmentioning
confidence: 62%
“…The crotalaria is used for the green manure and cover crop (Rosa et al 2004;Castro et al 2005) as an controlling nematode agent and as a fiber for the tobacco industry (Nogueira et al 1992). The definition of the pest thermal requirements has helped the pest management programs to predict the pest occurrence (Nava and Parra 2003) and to mass-rear the natural enemies for the applied biological control programs . In this study on the biology of U. ornatrix reared on the artificial diet in laboratory the thermal requirements for each insect's development stages in the laboratory were determiner.…”
Section: Introductionmentioning
confidence: 99%
“…A previsão de ocorrência da praga, com base nas exigências térmicas, pode melhorar a eficiência de controle. A utilização de modelos de graus-dia de laboratório tem auxiliado os programas de manejo (Higley et al, 1986;Ávila et al, 2002;Nava & Parra, 2003), e tem permitido conhecer a dinâmica populacional de pragas, determinar com mais eficiência a época de amostragem e definir o número de gerações delas.…”
Section: Introductionunclassified